Diagnostic Performance of Superb Microvascular Imaging and Other Sonographic Modalities in the Assessment of Lateral Epicondylosis. (29th August 2017) - Arslan, Serdar; Karahan, Ali Yavuz; Oncu, Fatih; Bakdik, Suleyman; Durmaz, Mehmet Sedat; Tolu, Ismet
Abstract : Objectives: The aim of this study was to compare the diagnostic performance of different sonographic modalities for diagnosing lateral epicondylosis. Methods: A total of 50 symptomatic and 50 asymptomatic common extensor tendons in 44 patients with lateral epicondylosis, and 25 healthy participants were prospectively examined by B‐mode sonography, color Doppler imaging, power Doppler imaging, Superb Microvascular Imaging (SMI; Toshiba Medical Systems Corporation, Tokyo, Japan), and strain elastography. We evaluated blood flow in common extensor tendons by using a grading system with color Doppler imaging, power Doppler imaging, and SMI. The diagnostic performance of the modalities was compared. Results: When a cutoff value of hypoechogenicity was used for the mean strain ratio, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy rates were 92.0%, 94%.0, 93.9%, 92.2%, and 93.0%, respectively. When a cutoff point of grade 1 was used, the sensitivity, specificity, PPV, NPV, and accuracy rates were 26.0%, 10.0%, 10.0%, 57.5%, and 63.0, for color Doppler imaging; 40.0%, 10.0%, 10.0%, 62.5%, and 70.0% for power Doppler imaging; and 84.0%, 94.0%, 93.0%, 85.5%, and 89.0% for SMI. When a cutoff value of 3.94 was used for the mean strain ratio, the sensitivity, specificity, PPV, NPV, and accuracy rates were 78.0%, 92.0%, 90.7%, 80.7%, and 85.0%, respectively. A statistically significant correlation was detected between SMI, strain elastography, and visual analog scale scores ( P < .001). Conclusions: The combination of SMI and B‐mode sonography was found to have excellent diagnostic performance for lateral epicondylosis. Neovascularzation in patients' tendons with lateral epicondylosis was identified much better with SMI compared to color or power Doppler imaging.